Snow Cover Change as a Climate Indicator in Brunswick Peninsula, Patagonia - Aguirre, Francisco; Carrasco Cerda, Jorge Fernando; Sauter, Tobias; Schneider, Christoph; Gaete, Katherine; Garin, Enrique; Adaros, Rodrigo; Butorovic Alvarado, Nicolas Santiago; Jana, Ricardo; Casassa, Gino (My University, 2018)
Snow cover changes are assessed for the Brunswick Peninsula in southern Patagonia (52.9 degrees S to 53.5 degrees S), located on the transition between the wet Pacific Ocean area and the drier leeward side of the Andes. We use the Normalized Difference Snow Index (NDSI) and a new index which we call Snowpower, combining the NDSI and the Melt Area Detection Index (MADI), to reconstruct the snow cover extent and its temporal distribution for the period 2000-2016, based on Moderate Resolution Imaging Spectroradiometer Sensor (MODIS) MOD09GA products. Comparison of these satellite-derived products with available snow duration and snow height data for 2010-2016 at the local Club Andino ski center of Punta Arenas shows that the NDSI exhibits the best agreement. A reasonable and significant linear correlation is found between the MODIS NDSI snow cover extent and the mean monthly temperature at Punta Arenas Airport combined with the monthly snow accumulation at Jorge Schythe station at Punta Arenas city for the extended winter period (April to September) from 2000 to 2016. Snow cover changes within this time series are extended to 1972 and 1958 based on historical climate data of Jorge Schythe and Punta Arenas airport, repectively. The results show a significant decreasing trend of snow extent of 19% for Brunswick Peninsula for the 45-year period (1972-2016), which can be attributed to a statistically significant long-term warming of 0.71 degrees C at Punta Arenas during the extended winter (April-September) in the same period. Multiple correlation with different climate variables indicates that solid precipitation has a relevant role on short-term snow cover variability, but is not related to the observed long-term snow cover decrease.
Keywords: snow cover; climate change; remote sensing; modis; patagonia